Effectiveness of cinnamon (Cinnamomum zeylanicum) bark oil in the prevention of carbon tetrachloride-induced damages on the male reproductive system - Yuce, A.; Turk, G.; Ceribasi, S.; Guvenc, M.; Ciftci, M.; Sonmez, M.; Aksakal, M. (Wiley-Blackwell, 2014)
In this study, it was aimed to investigate the likelihood of detrimental effects of carbon tetrachloride (CCl4) on male reproductive system through oxidative stress mechanism and also protective effects of cinnamon bark oil (CBO). For this purpose, 28 healthy male Wistar rats were divided into four groups, seven rats in each. Group 1 received only olive oil daily; group 2 was treated with 100mgkg(-1) CBO daily; group 3 was treated with only 0.25mlkg(-1) CCl4 weekly; and group 4 received weekly CCl4+daily CBO. All administrations were made by intragastric catheter and maintained for 10weeks. Body and reproductive organ weights, sperm characteristics, testicular oxidative stress markers and testicular apoptosis were examined. CCl4 administration caused significant decreases in body and reproductive organ weights, testicular catalase (CAT) activity, sperm motility and concentration, and significant increases in lipid peroxidation (LPO) level, abnormal sperm rate and apoptotic index along with some histopathological damages compared with the control group. However, significant improvements were observed in absolute weights of testis and epididymis, all sperm quality parameters, LPO level, apoptotic index and testicular histopathological structure following the administration of CCl4 together with CBO when compared to group given CCl4 only. The findings of this study clearly suggest that CBO has protective effect against damages in male reproductive organs and cells induced by CCl4.
Keywords: Apoptosis; carbon tetrachloride; cinnamon bark oil; lipid peroxidation; sperm; testis